Communication during Covid‐19: Impacts of face coverings on people living with dementia. (December 2021) - Jeong, Tina Hyerim; Volkmer, Anna; Jiang, Jessica; Brotherhood, Emilie V; Dobson, Lucianne; Harding, Emma; Suarez‐Gonzalez, Aida; Crutch, Sebastian J; Warren, Jason D; Hardy, Chris JD; Agustus, Jennifer L
Abstract: Background: The compulsory introduction of wearing face coverings and social distancing to curb the spread of Covid‐19 in the United Kingdom has reduced both the quality of auditory information and availability of visual and non‐verbal cues during conversations with others. This is likely to have a greater impact on efficiency and effectiveness of communication for people living with dementia and particularly those with a language‐led dementia: Primary Progressive Aphasia (PPA). Method: Twenty‐four people living with dementia (PLWD), 95 caregivers (on behalf of PLWD) and 38 healthy older controls anonymously reported their experiences of wearing face coverings and the associated impacts on communication via an online survey that ran between December 2020 and April 2021 (age ranges: PLWD 38‐90 years; controls 32‐100 years). The majority of questions were self‐reflective experiences compared to when not wearing face coverings. Mann‐Whitney U tests were used to compare Likert ratings for impact of wearing face coverings on aspects of speaking, listening and holding conversations between PLWD or diagnosis subgroups (27 PPA; 26 Frontotemporal Dementia, FTD; 29 Alzheimer's disease, AD; 24 Posterior Cortical Atrophy, PCA) and the controls. Result: Wearing a face covering made both speaking (80%) and listening (90%) more effortful for the majority of survey respondents and had a greater impact on people living with PPA. Overall PLWD were more likely to require help communicating and those with PPA relied more on non‐verbal strategies (e.g. body language or gestures) than when not wearing a face covering, compared to controls (p=0.001) and other diagnosis subgroups. People with PPA also experienced greater difficulty understanding across diverse everyday listening conditions and most aspects of conversation than controls (p<0.05). People with PCA (p=0.039) also had more difficulty knowing when it was their turn to speak and those with FTD had more difficulty speaking over others (p=0.032), compared to controls. The use of face coverings during the Covid‐19 pandemic also prevented more PLWD from taking part in activities than controls. Conclusion: PLWD, and in particular those with a diagnosis of PPA, are particularly susceptible to the negative impacts of the use of face coverings on communication.